Transformasi Digital Dalam Pelayanan Notaris: Analisis Hukum Terhadap Keabsahan Akta yang Dibuat Secara Elektronik - Ramadhan, A’ishah Mutiara (CV. Rayyan Dwi Bharata, 2025)
This study examines the legal framework governing electronic deeds in Indonesia’s notarial practice through a normative juridical approach, supported by statutory, conceptual, historical, and comparative analyses. It focuses on the regulatory gap between the Notary Position Act (UUJN) and the Electronic Information and Transactions Act (UU ITE), which creates uncertainty regarding the validity of electronic notarial deeds. Using Gustav Radbruch’s Theory of Legal Certainty, the research emphasises the need for clear and reliable laws to support digital transformation in notarisation. Comparative analysis includes Remote Online Notarization (RON) in the United States and digital notary systems in the Netherlands and Australia, highlighting mechanisms such as blockchain technology and interoperable digital platforms. The study proposes harmonising Indonesian regulations, adopting secure technologies, and enhancing notaries’ competencies to ensure security and legal recognition of electronic deeds. These measures aim to provide legal certainty and protect stakeholders in Indonesia’s evolving digital notarial landscape.